Mobile ad hoc networks problem - a queueing approach. (2018) - Maragathasundari, S.; Dhanalakshmi, K.S.
This paper investigates a study on mobile communication network by means of queuing theory approach. The good QOS in mobile communication network is necessary at this, the presence financially viable situation of global economic meltdown and competitive business environment with low tariff. In order to endure in this present economic situation, the network operators must put into consideration the effective use of their available resources. Due to technical error such as electromagnetic causes, irregular user behaviour, etc. the calls are truncated during conversation. Also the congestion is caused when the offered load of the network is more than the available resources. This problem of congestion and other breakdown occurring in MANET is approached through queueing theory in this study. Queueing attitude defines the slip-up in the networking and gives out the required ideas to be passed out to minimise the error occurring resources. It also introduces the concept of preservation period after the completion of service. Numerical illustration and an elaborate graphical study are carried out at the end to validate the model. It gives a clear thought about the conceptual study of queueing theory in mobile ad hoc networks.